Analisis Implementasi Manajemen Sistem K3 Dalam Upaya Pencegahan Resiko Kecelakaan Kerja di PT. X - Angraeni, Nur; Yudhanegara, Darmawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The main factors causing K3 violations include lack of supervision, discomfort in using PPE, and the lack of strict sanctions for violators. As a solution, companies can increase supervision through routine inspections, provide regular training, and implement a clearer incentive and sanction system to increase worker compliance with K3 regulations. The implications of this research point to the need to improve work safety culture in companies by involving all organizational elements in implementing SMK3. In this way, it is hoped that the risk of work accidents can be minimized and a safer and more productive work environment can be created.